ROLE OF THE INDUSTRIAL AND LABOR SERVICES OF KAMPAR REGENCY IN INDUSTRIAL RELATIONS DISPUTE SETTLEMENT - Afrinaldy Rustam; Nadya Anastasya Wiyanto (Indonesian Journal of Social Sciences, Policy and Politics, 2023)
This study aims to determine the role of the Kampar District Office of Industry and Labor in the process of settling industrial relations. In addition, the author also wants to know the obstacles in the process of resolving industrial relations equations. The research technique used is a qualitative research method with direct interviews, observation, and documentation related to research. From this research technique, informants were obtained consisting of the Head of the Industry and Labor Office of Kampar Regency, the Head of the Industrial Relations Section, the Head of the Industrial Relations Section, Mediators, companies and workers. Based on the research conducted, it is known that functional officials, namely section heads, are mediators who play a role in fostering industrial relations. The Department of Industry and Labor of Kampar Regency lacks technical personnel, namely only 1 (one) mediator.